Appendectomy and risk of Parkinson's disease: A nationwide cohort study with more than 10 years of follow‐up. Issue 12 (13th September 2016) - Svensson, Elisabeth; Horváth‐Puhó, Erzsébet; Stokholm, Morten Gersel; Sørensen, Henrik Toft; Henderson, Victor W.; Borghammer, Per
ABSTRACT: Objectives: The appendix may be a key site for the initiation of Parkinson's disease (PD) pathology. We examined the hypothesis that appendectomy is associated with lower PD risk. Methods: We used Danish medical and administrative registries to construct a cohort of all patients in Denmark with an operation code of appendectomy during 1980‐2010 (n = 265, 758) and a matched general population comparison cohort (n = 1, 328, 790). Using Cox regression, we computed hazard ratios and corresponding 95% confidence intervals for PD, adjusting for potential confounders and stratifying on age at appendectomy (≤45 years / > 45 years), sex, and follow‐up time. Results: During follow‐up ( > 10 years), PD incidence was 0.19 and 0.15 per 1, 000 person‐years at risk in the appendectomy cohort and in the general population comparison cohort, respectively, yielding a slightly increased risk of PD (adjusted hazard ratio = 1.14; 95% confidence interval 1.03‐1.27). Findings were consistent after more than 20 years of follow‐up and when stratified on age of appendectomy and sex. Conclusion: Appendectomy was associated with a small increase in PD risk 10 or more years after surgery. © 2016 International Parkinson and Movement Disorder Society